Comparative Study of the Potential of Sorong City Sand and Tobelo Sand as Concrete Material - Fajar, Muhammad Nur; Arifin, Herlina; Purwantoro, Didik Setya; Rusdi, Achmad (Universitas Negeri Padang, 2023)
The quality of the sand used for the concrete mixture can affect the compressive strength produced by the concrete. This study aims to determine the amount of compressive strength and modulus of elasticity of concrete with quarry sand material Km.14 Sorong City and sand quarry from other regions, namely Tobelo North Halmahera quarry sand. This study used an experimental method with a total of 18 selinder-shaped test objects consisting of 3 samples aged 7 days, 3 samples aged 14 days and 3 samples aged 28 days for each quarry Modulus of elasticity testing was only carried out on concrete aged 28 days. All material testing until the manufacture and tests of compressive strength and modulus of elasticity of cylindrical samples are carried out at the Civil Engineering Concrete Laboratory of the University of Muhammadiyah Sorong. From the results showed the average compressive strength produced between sand Km.14 of Sorong city and Tobelo sand was 8.78 Mpa: 11.13 Mpa for 7 days old, 10.66 Mpa: 12.83 Mpa for 14 days old and 11.23 Mpa: 13.78 Mpa for 28 days old. In addition, based on concrete strain testing, it can be seen that the higher the compressive strength or stress of the concrete, the higher the strain value.